VLF/LF Reflectivity of the Polar Ionosphere. - Pagliarulo,Robert P; Turtle,John P; Rasmussen,John E; Klemetti,Wayne I (1980)
This report provides a summary of high latitude ionospheric reflectivity as observed by the USAF high resolution VLF/LF ionosounder operating in northern Greenland. Ionospheric reflectivity parameters, including reflection heights and coefficients, are presented as a function of time of day. Riometer and magnetometer measurements of the polar propagation environment are presented as supplementary data. (Author)